Seki, founder of modern mathematics in Japan : A commemoration on his tercentenary - Komatsu, Hikosaburo; Liu, Dun; Knobloch, Eberhard (Springer Proceedings in Mathematics & Statistics, 2013)
Seki was a Japanese mathematician in the seventeenth century known for his outstanding achievements, including the elimination theory of systems of algebraic equations, which preceded the works of Étienne Bézout and Leonhard Euler by 80 years. Seki was a contemporary of Isaac Newton and Gottfried Wilhelm Leibniz, although there was apparently no direct interaction between them. The Mathematical Society of Japan and the History of Mathematics Society of Japan hosted the International Conference on History of Mathematics in Commemoration of the 300th Posthumous Anniversary of Seki in 2008. This book is the official record of the conference and includes supplements of collated texts of Seki's original writings with notes in English on these texts. Hikosaburo Komatsu (Professor emeritus, The University of Tokyo), one of the editors, is known for partial differential equations and hyperfunction theory, and for his study on the history of Japanese mathematics. He served as the President of the International Congress of Mathematicians Kyoto 1990.